The Impact of Embracing E-Business on the Competitive Edge of Small and Medium-Sized Enterprises - Marwah, Al zoubi A.; Belal, Al-Nsour H.; Faten, Al-Tahayneh W. (Migration Letters, 2023)
Numerous studies have attempted to define effective strategies for examining how small and medium-sized businesses (SMEs) evaluate competitive advantage. This is particularly relevant due to the heightened competition for investment funds in projects. However, achieving a competitive edge in trade has remained unattained in Amman, Jordan. This is evident from analyses of cost-effectiveness and assessments of supply chain operations within SMEs. These evaluations reveal a disconnect between operational production management and the technological capabilities needed to foster competitive advantages. The intricate nature of producing unique goods and services further complicates matters. The primary aim of this research is to provide insights to researchers and policymakers about the influence of E-Business Adoption on SME competition. The study seeks to uncover several perspectives through its analyses and arguments regarding the adoption of e-business practices by SMEs. By employing a deductive approach in a quantitative research framework, the study integrates exploratory research, which is crucial in developing comprehensive marketing or business strategies. This step aims to shed light on the degree to which E-Business Adoption impacts SME competition in Amman, Jordan. Through the utilization of structural equalization modeling—a sophisticated multivariate statistical analysis technique—the study’s findings reveal a statistically significant relationship between E-Business Adoption and the competitive advantage of SMEs in Amman, Jordan. E-Business Adoption comprises three distinct components: the necessity for Electronic Marketing, Online Customer Communication, and online order taking. These elements collectively exert a substantial impact on SME competition. Among these dimensions, Electronic Marketing has the most profound influence, while the impact of online order-taking is relatively moderate. In light of these findings, the study emphasizes the significance of SMEs actively considering the integration of online order-taking mechanisms as part of their E-Business Adoption strategy, thereby heightening their overall competitive advantage.